2021
DOI: 10.1097/md.0000000000026713
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronavirus disease 2019 on patients with toothache

Abstract: Objective: The aim of this study is to investigate the impact of Coronavirus disease 2019 (COVID-19) on toothache patients through posts on Sina Weibo. Methods: Using Gooseeker, we searched and screened 24,108 posts about toothache on Weibo during the dental clinical closure period of China (February 1, 2020–February 29, 2020), and then divided them into 4 categories (causes of toothache, treatments of toothache, impacts of COVID-19 on toothache treatment, popular scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…There was also an increase reported in the use of online searches and social media to address/express oral healthrelated concerns during the pandemic [62,[105][106][107][108][109]. Two studies explored key search terms utilised by those searching online with results showing that "toothache" and "corona-toothache" were used most frequently [105,109].…”
Section: Alternative Models Of Dental Provision and Online Help-seekingmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also an increase reported in the use of online searches and social media to address/express oral healthrelated concerns during the pandemic [62,[105][106][107][108][109]. Two studies explored key search terms utilised by those searching online with results showing that "toothache" and "corona-toothache" were used most frequently [105,109].…”
Section: Alternative Models Of Dental Provision and Online Help-seekingmentioning
confidence: 99%
“…One study focused on the use of Twitter throughout the pandemic with people tweeting about oral health impact, types of dental problems, managing symptoms at home, views on consequences of delaying dental treatment and experiences with accessing oral health services [106]. A similar study carried out using the Weibo platform found 12,603 posts related to toothache with 38.9% posts indicating that treatment for dental pain was affected by COVID-19 with many indicating that they couldn't visit their dentist due to clinic closures [108]. Searches for "teledentistry" and "PPE were also popular [45].…”
Section: Alternative Models Of Dental Provision and Online Help-seekingmentioning
confidence: 99%